IMPACT OF E-MARKETING ON CONSUMER BUYING BEHAVIOUR (International Journal of Food and Nutritional Sciences, 2022)
The speedy boom of e-marketing and net is implementing profound impacts on customer conduct and cutting-edge society. This studies seeks to investigate the effect of e-advertising on customer shopping for conduct within side the foremost towns of Kanyakumari District in Tamilnadu . The pervasiveness of e-advertising influences how, where, and while purchasers store on line and impacts the preferences, selections and manner of existence of purchasers. Online buying is the a part of existence fashion of people. Why purchasers buy a few items and now no longer purchases different items is hard to apprehend. It is important to look at the effect of e-advertising on purchasers’ e- shopping for conduct. The modern studies has attempted to apprehend the mindset toward e-advertising, look at the effect of demographic elements, what kind of merchandise they purchase and what elements impacts customer shopping for conduct. Sample of 455 respondents of drawn from 5 towns in Kanyakumari District, i.e., Nagercoil, Marthandam, Colachel, Thakalay and Monday market. The facts can be amassed thru questionnaire approach and with the aid of using taking a few direct interviews of respondents